Social development for the Cape Flats: an alternative planning structure - Paton, Hugh M (Urban Management, 2019)
An initial analysis into the present problems which will affect the future growth of the Western Cape resulted in the conclusion that the situation of the Coloured population is the factor most urgently requiring positive planning resolutions. Understanding the area's problems leads one to conclude that the main thrusts must be directed towards increased opportunities for the residents to fulfil their potential, and towards a greater involvement in the decisions made about their future. The arrangement of the thesis was thus developed around the three interrelated notions of administrative structure, human resources and social development, physical and economic resources. An unbound 'process diagram’ is provided in the back cover to facilitate an understanding of the sequence adopted. The administrative and planning activities of various local authorities, particularly the Cape Town City Council, were investigated with respect to the relationship between their actions and the causes of problems on the Flats. The complexity of social problems necessitated a consideration of the concept and the theory of social development. This was defined as the process whereby the individual and/or group is enabled to increasingly participate in and contribute to the growing flow of social transactions over time. By adopting Social Development as the goal for the Cape Flats and developing objectives for its six primary subsystems (housing, education, employment, recreation, community and civic), the subsequent form of the thesis was established.